Service Quality in Nepalese Insurance Market - Lohani, Sharda Pandi; K.C., Fattah Bahadur (Nepalese Journal of Insurance and Social Security, 2018)
The present study focuses on measurement of customers’ satisfaction level in Nepalese insurance market by comparing customers’ perceived service quality and expectations. The questionnaire for customers’ perceptions and expectations were prepared common for both life and non-life insurance companies. The data is being collected through a framed questionnaire which was totally sculpted based on the SERVQUAL model. For this study, 9 life insurance Companies, 17 non-life insurance companies, and 1 Reinsurance Company were selected for response of customers’ satisfaction level. The five dimensions of SERVQUAL are tangibility, reliability, responsiveness, assurance, and empathy. The customers perceive the service quality to be high if it is perfect on their expectation and it leads to their satisfaction with the related service. In this paper, primary data collected from the Kathmandu valley is the descriptive analysis of the life and non -life insurers in Nepalese insurance market. The study finds the gap between the expectations and perceptions of customers in Nepalese insurance market.